MANAJEMEN PERKAWINAN KUDA DI TOMBO ATI STABLE SALATIGA JAWA TENGAH - , NURUL HIDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Field practice on Tombo Ati horse Stable which located in the Butuh village, District Tengaran, Semarang regency was done to observe horse mating management. The purpose of this thesis was structured to determine mating management Tombo Ati Stable. Material used was activities that conducted in management of horse mating at Tombo Ati Stable on December 24 to March 29, 2014. Methods used for data collection were observation, interviews with the person in charge, picture taking and direct practice for at Tombo Ati Stable. Activities undertaken for recording were the time of puberty, estrus detection, estrus cycle, the regulation of marriage. The observation result of mating management of horses in Tombo Ati Stable was a complete recording form. Puberty or sexual maturity occurs at age 12-15 months, detection of estrus using teaser was done by walked it near the stallionâs cage, long estrus 4 to 6 days with a 21-day estrous cycle. Mating horses performed at age 4 to 6 years. Horse mating method is done naturally by using Thoroughbred and Indonesian Race Horse (KPI) in order to maintain the clarity of genealogical (pedigree). Mating Management in Tombo Ati stable is good, according to the literature only after the rest period should be mated racehorse retirement after a 6 month break so that the development of the reproductive organs more perfect.